The Impact of Emotional Intelligence on Conflict Management Case Study from Jordan - Alomari, Ghassan Issa; Alnajdawi, Sakher; Al-Mansour, Ammar Yaser Mansour; Hanandeh, Rami (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to explore the impact Emotional Intelligence on Conflict Management in The Jordanian Securities Commission (JSC). To produce numeric data as well as to test the hypothesis, the researchers use the statistical package for social science (SPSS). The testing included (N=320) questionnaires. Our suggested model examined The Jordanian Securities Commission (JSC) located in Amman-Jordan. The main results show that Emotional Intelligence has moderately to weak impact on Conflict Management for the managers, vice manager and Assistant Manager whom work in the Jordanian Securities Commission. This study contributes to the existing limited research on the topic. However previous researches offered an important base for the study regarding the consequences of emotions on conflict management; nevertheless, they have not addressed the particular approaches that people are more likely to use when confronted with conflict. This study explores the link between the Emotional Intelligence and all the five styles of Conflict Management, which’s need more empirical investigations, as well as this study offered number of recommendations for future research.